The use of content marketing on the websites of dairy companies - Strzębicki Dariusz (Marketing of Scientific and Research Organizations, 2022)
This article’s aim is an attempt to identify the scope and ways of implementing content marketing on the websites of dairy companies. To achieve the stated objective, 15 dairy company websites were analysed using the content analysis method. It was observed that the companies surveyed use content marketing in different ways on their company websites, with the aim of distributing attractive content designed to persuade the customer to act accordingly. Companies are recognising the increasing role of content marketing and the opportunities for its implementation on the company website. However, there is great potential to intensify activities in this area.